Histórias de vida e formação: análise de relatos de professores licenciados em Matemática pela Ead/Unitins - Moraes, Carlos Wiennery da Rocha (Universidade Federal do Tocantins, 2016)
Studies involving teachers formation have been privileged in education with a view to terminating the complex challenges that are presented in a context broad and heterogeneous as the country. This work cuts the universe of distance education in Tocantins and, in this way, addresses issues incipient by academic research. The research reported discussion about life stories and training in distance graduation of four teachers from the University of Tocantins. Thus, in discursive movement we ask: how teachers recently graduated from distance education by UNITINS mean this type of education in the discursive movement, outlined by reports of their life stories. Based on this question, our overall goal was to analyze the speeches of the formation of these subjects, their expectations regarding schooling, the meanings that attach along their lives to education and identities that build on these subjects training. We pointed out aspects that outline the training received, the difficulties encountered, the paths that travel through higher education and the expectations arising from the recently teachers formation. Guided by Discourse Analysis and the technique of life story, we bring the real emerges as an effect of discourse: that school is that they talk about and which correspond so many expectations of democratization of access to socially valued knowledge? We believe that the stories of individuals, despite their quirks, are crossed by a collective history. The results lead us to conclude that the stories are similar and suggest some regularities and for a story lived collectively. The research subjects have in common membership in the same social class, They share a bumpy trajectory of schooling Naturalizesitselfin the imaginationof these subjects, in principle, distance learningas the possibilitythatpresents them withmoreease of entryandthe short duration,becauseof their work. The education offered, however, not promises great advances in terms of gain for the quality of learning of the respondents. The model presents silent, vertical, instructional, surpassed only by the horizontality of exchange and dialogue among peers, produced without the knowledge of what was planned. Althoughthe speechof distance education in principle seeks to promote the democratization of access to knowledge, research shows that there is no way he wave necessarily attest to success in learning. There are gaps that need to receive more attention in order to more symmetric models of teaching and learning, guided by effective interaction and collaboration.